Long-term changes in spatio-temporal heterogeneities of vegetation greenness and land surface temperature in China - Rui Yao; Yongjie Li; Tingting Ma; Minfeng Yuan; Zhihao Zhang; Siyuan Chen; Chuan Wang; Binghan Wang; Zhenyu Fu; Hengwei Li (Remote Sensing Applications: Society and Environment, 2026)

Shape-dependent magnetic-driven microrobots for biofilm-eradicating medical device disinfection through mechanical and chemical bactericidal action - Ke Cheng; Tongfang Fu; Shan Sun; Wenhao Zheng; Jiaming Gong; Jingxin Ma; Yazhou Zhou; Feili Lai; Martin Pumera; Hengwei Lin (Chemical Engineering Journal, 2026)

A high-strength, heat-resistant, recyclable, and degradable ramie fiber-reinforced polyimine biocomposite - Pandeng Li; Tingting Liu; Gen Lu; Tong Shu; Tianyi Yu; Yuchen Zhao; Hengwei Fu; Junqi Yang; Haoping Du; Penghao Sun; Ziqi Hou; Chunhua Fu; et al. (Chemical Engineering Journal, 2026)

Production and characterization of monoclonal antibodies against mandarinfish ranavirus and first identification of pyloric caecum as the major target tissue - Wenfeng Zhang; Hengwei Deng; Yuting Fu; Weixuan Fu; Shaoping Weng; Jianguo He; Chuanfu Dong (Journal of Fish Diseases, 2023)
Mandarinfish ranavirus (MRV), also known as a variant of largemouth bass virus (LMBV), is an emerging pathogen in mandarinfish aquaculture. In this study, monoclonal antibodies (mAbs) against MRV were produced and characterized, and 7 mAbs were obtained through Western blotting screening and all 7 mAbs specifically recognized MRV/LMBV but not several piscine iridoviruses as ISKNV, GIV and TFV. By LC MS/MS analysis, the recognized viral proteins by seven mAbs were identified as MRV‐pORF47L, MRV‐pORF55R, MRV‐pORF57L, MRV‐pORF77L and MRV‐pORF78L, respectively, and all five viral proteins are late expression structural proteins by Western blotting. Based on mAb 1C4, immuno‐histochemistry and immuno‐histo‐fluorescence were performed to re‐assess the tissue tropism of MRV. The result showed that abundant reactive signals were observed in infected spleen, kidney as well as intestine and pyloric caecum. Real‐time quantitative PCR also demonstrated that spleen as well as pyloric caecum and intestines are the major target tissue upon MRV infection. In infected intestines and pyloric caecum, numerous enlarged, multinucleated cells with intracytoplasmic inclusions were identified as the target cells of MRV, suggesting that MRV serves as a digestive tract pathogen to mandarinfish, which may explain why acute infection of MRV can cause the typical clinicopathology featured by severe ascites.

Multi-Omics Study on the Molecular Mechanisms of Tetraodon Nigroviridis Resistance to Exogenous Vibrio Parahaemolyticus Infection - Shoujia Jiang; Lijun Fu; Zijian Gao; Hengwei Deng; Yong Zhang; Xinxin You; Qiong Shi; Danqi Lu (Frontiers in Marine Science, 2022)
Vibrio parahaemolyticus is an important marine pathogen that causes inflammation and even death in teleost fishes. It has brought significant economic losses to the aquaculture industry as well as high risks to the sustainable development of marine fisheries. In the present study, the fish Tetraodon nigroviridis and the bacterial pathogen Vibrio parahaemolyticus were used to explore the molecular mechanisms underlying the immune response of T. nigroviridis to V. parahaemolyticus exogenous infection. The microRNA (miRNA)–mRNA–protein omics and corresponding experimental validation, followed by comparative analysis, revealed several differentially expressed genes involved in various components of the immune system, including the following: complement system, chemokines, lysosomes, phagocytes, B-cell receptor signaling pathway, T-cell receptor signaling pathway, Janus kinase-signal transducer and activator of transcription (JAK-STAT) signaling pathway, and phospholipid metabolism, among others. Especially, the complements component 3 (C3) gene and protein expression levels were significantly higher after V. parahaemolyticus infection, and miRNAs targeting C3, including mir-6089-y, mir-460-y, and mir-1584-x, were significantly down-regulated. The gene and protein expression levels of complement 1 subunit qA (C1qA) were significantly down-regulated, while mir-203 targeting C1qA was significantly up-regulated. Overall, four complement genes (C1qA, IG, C3, and C5) , which are key genes in the classical pathway of complement system activation for inflammatory response, were identified. Evolutionary analysis suggested that T. nigroviridis, acquired an increased ability to recognize pathogens by evolving a more complex complement system than terrestrial vertebrates. In addition, quantitative real-time polymerase chain reaction showed high consistency with the obtained multi-omics results, indicating the reliability of the sequencing data generated in the present study. In summary, our findings can serve as a fundamental basis for further in-depth multi-omics studies on the inflammatory processes of aquatic pathogens hindering fish sustainable production.